Simple Synthesis Method and Characterizations of Aggregation-Free Cysteamine Capped PbS Quantum Dot - Daekyung Kang; Mareddi Bharath Kumar; Changhee Son; Hongsik Park; Jonghoo Park (Applied Sciences, 2019)
Quantum dots have diverse chemical properties with different ligands attached on the surface. The cysteamine has been used as a ligand for various quantum dots because it has high solubility in water, and it facilitates binding of quantum dot and gold surface. However, the hydrogen bonds in cysteamine cause aggregation of the cysteamine capped quantum dots. In this study, we suggested a simple synthesis method of aggregation-free PbS quantum dot and analyzed the electric and optical properties of the synthesized quantum dot. This study on aggregation-free cysteamine capped quantum dots has the potential to develop advanced quantum dot-based sensor technologies, including biomedical imaging and environmental sensors.